Novel halogen-free flame retardants - flame retardation of unsaturated polyester resins with use of boron compound - Kicko-Walczak, E. (Polimery, 2022)
The efficiency of boron compounds as novel halogen-free flame retardants (FR) for unsaturated polyester resins (UP) has been examined. Selected types of FR (both crystalline and liquid ones) were used in properly chosen amounts (Table 1). The effects of FR addition on flammability level and thermal stability of compositions and polyester-glass laminates were determined by oxygen index measurements, thermogravimetric analysis and cone calorimetry (Table 2 and 3, Fig. 1-3). Gelation time and viscosity of the compositions before curing were also measured as well as mechanical properties of the cured compositions (Table 4). It was found that boron compounds used as flame retardants retard the UP burning and change the material behavior in the flame. The same time they do not deteriorate physical and strength properties of cured resins.